Experiences and Perceptions of Crisis Text Services: Interview Study Among Young Adults With Suicidal Ideation - Kate LaForge; Alan R Teo; Lauren Denneson; Jennifer A Hoffmann; Peter C Britton; Ashley A Foster (JMIR Mental Health, 2026)
Abstract Background Suicide remains a leading cause of death among young adults aged 18 to 25 years. Young adults experiencing suicidal ideation (SI) are increasingly using crisis text services (CTSs), a free and accessible option for crisis intervention. Little is known about CTSs from the young adult perspective. Objective This study aimed to characterize young adults’ experiences with and perceptions of CTSs for SI. Methods We conducted in-depth interviews, by phone, Zoom, or text, with young adults (n=39) in the United States who had a lifetime history of SI. Participants included those who had or had not engaged with CTSs for SI. Semistructured interviews were conducted from January to July 2024. The data were analyzed using a modified grounded theory approach. Results We constructed 5 key themes to characterize young adults’ perceptions of and experiences with CTSs for SI. Young adults perceived CTSs as a unique component of their mental health crisis management. They appreciated CTSs’ technological features, particularly the privacy they provided and the ability to reflect on and edit responses. However, they expressed dissatisfaction with the nonspecific nature of many CTS interactions. The perceived anonymity of CTSs served multiple functions, both as a motivator for CTS use and as a potential point of vulnerability, should it be lost during a CTS interaction. Participants’ perceptions of CTSs’ impact varied; some viewed them as beneficial, whereas others reported neutral or inconsistent effects over time. Conclusions Among young adults with SI, CTSs are a key yet imperfect resource. Quality improvement and evaluation efforts may be needed to understand how responders can better tailor responses to improve conversational quality and consistency for young adult texters.